Estimating the Impact of Occupants' Behaviour on Energy Consumption by Pls-SEM: A Case Study of Pakdel Residential Complex in Isfahan, IRAN - Tavakoli, Elahe; Nikkhah, Arman; Zomorodian, Zahra Sadat; Tahsildoost, Mohammad; Hoonejani, Mohammad R. (Frontiers in Sustainable Cities, 2022)
The importance of energy saving in current decade has drawn more attention to optimising energy consumption factors. One of the influential and well-known factors affecting energy consumption is the occupants' behaviours (OBs). Reviewing this factor is a requirement to assess buildings, particularly the residential sector, as the majority target of the building industry. In this study, occupants' energy behaviours in Shahid Pakdel residential complex in Isfahan, Iran, is studied based on Annex 53 questionnaire and building performance simulation (BPS). The main objective of this study is to identify the impact of apartment improvement and OBs, including windows opening, curtain controlling behaviour, and turning on heating equipment in the cold season on energy consumption. Due to the invisible effect of some behaviours, especially for gas consumption (GC) and electricity consumption (EC), structural equation modelling (SEM) is applied to evaluate the impacts of OBs. This case study showed that the most influential behaviour factor is related to the improvement sector with 41.7% share of EC. Moreover, the most negligible influential factor is associated with windows opening with 21.6% of the EC. Regarding GC, the most and the least determining behaviour factor were attributed to apartment improvement and curtain controlling behaviour with an effective rate of 64.5% and 5%, respectively. This result showed the high impact of apartment improvement on reducing GC and EC. The overall effect of behaviour on GC and EC was 46% and 44%, respectively, measured by the partial least squares (PLS) regression and R2 score.